2016
DOI: 10.1103/physrevd.94.054030
|View full text |Cite
|
Sign up to set email alerts
|

Strong decays of theX(2500)newly observed by the BESIII Collaboration

Abstract: Basing on the observation of a new J P C = 0 −+ state, X(2500), in the partial wave analysis of the decay J/ψ → γX → γφφ performed by the BESIII Collaboration, we have evaluated the strong decays of the X(2500) as the 4 1 S0 and 5 1 S0 ss states in the 3 P0 model of meson decay. The predicted total decay width for the 4 1 S0 ss is about 894.5 MeV, and the one for the 5 1 S0 ss is about 271.1 MeV, which is in agreement with the experimental data Γ X(2500) = 230 +64+56 −35−33 MeV. By considering the mass and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 45 publications
(52 reference statements)
4
29
0
Order By: Relevance
“…Also, both Eqs. (21) and (22) indicate that the η(2320) is mainly the nn, consistent with the π(2360) nearly degenerating with the η(2320), while the X (2500) is mainly the ss, consistent with our previous analysis [6]. Therefore, the η(2320) and X (2500), together with the π(2360), appear to be the convincing 5 1 S 0 states.…”
Section: Width Mevsupporting
confidence: 84%
See 3 more Smart Citations
“…Also, both Eqs. (21) and (22) indicate that the η(2320) is mainly the nn, consistent with the π(2360) nearly degenerating with the η(2320), while the X (2500) is mainly the ss, consistent with our previous analysis [6]. Therefore, the η(2320) and X (2500), together with the π(2360), appear to be the convincing 5 1 S 0 states.…”
Section: Width Mevsupporting
confidence: 84%
“…Among these states, the assignments of the π , η, η , and K as the members of the 1 1 S 0 meson nonet and the π(1300), η(1295), η(1475), and K (1460) as the members of the 2 1 S 0 meson nonet have been widely accepted [2]. In our previous works, we suggested that the π(1800), η(1760), X (1835), and K (1830) can be identified as members of the 3 1 S 0 meson nonet [4], the π(2070), η(2100), and η(2225) can be identified as the members of 4 1 S 0 meson [5], and the X (2500) is the mainly ss member of the 5 1 S 0 meson nonet [6], where the mixing of the X (2500) and its isoscalar partner is not considered and other a e-mail: wangen@zzu.edu.cn b e-mail: lidm@zzu.edu.cn members of the 5 1 S 0 meson nonet are not discussed. In this work, we shall address the possible SU(3) multiplet partners of the X (2500).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…[25, 26, 31-35, 39, 43-45], and the constituent quark masses are taken to be m u = m d = 330 MeV and m s = 550 MeV, as in Refs. [27,[31][32][33][34][35]39]. We take γ = 7.1 by fitting to the total width of a 0 (1450) as the 1 3 P 0 state.…”
Section: Calculation and Resultsmentioning
confidence: 99%